2009
DOI: 10.1177/104063870902100205
|View full text |Cite
|
Sign up to set email alerts
|

Baccharis Pteronioides Toxicity in Livestock and Hamsters

Abstract: Abstract. Baccharis pteronioides DC has been intermittently associated with livestock poisoning in the southwestern United States. In 2004, nearly 100 cows were reported poisoned by B. pteronioides in southern New Mexico. Initial field studies and postmortem examinations found drought conditions, evidence of B. pteronioides consumption, and a reported mortality of nearly 40%. Because postmortem materials were unsuitable for further examination, plant samples were collected for feeding trials and chemical evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…It is worth noting that the shrub species predominantly consumed by ashy chinchilla rat, B. tola, has already been reported in the diet of this species in northern Chile (Cortés et al, 2002b). Baccharis tola belongs to a genus composed of species toxic for some herbivores (Alda et al, 2009;Stegelmeier et al, 2009). Terpenes have been isolated from this species (San Martin et al, 1983), being the main secondary compounds of its resin (Langenham, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…It is worth noting that the shrub species predominantly consumed by ashy chinchilla rat, B. tola, has already been reported in the diet of this species in northern Chile (Cortés et al, 2002b). Baccharis tola belongs to a genus composed of species toxic for some herbivores (Alda et al, 2009;Stegelmeier et al, 2009). Terpenes have been isolated from this species (San Martin et al, 1983), being the main secondary compounds of its resin (Langenham, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…in livestock was never completely resolved (Barros 1998, Rissi et al 2005. It was suggested that dehydration, electrolyte imbalance and septicemia stemming from bacterial invasion through breakdowns in necrotic ruminal epithelium (Rissi et al 2005) and disseminated vascular coagulation (Stegelmeier et al 2009) could play a part. Data from the current experiment suggest that several of these mechanisms of disease production could act concomitantly or in sequence in the pathogenesis and cause of death of buffalo experimentally poisoned by B. megapotamica var.…”
Section: Discussionmentioning
confidence: 99%
“…This species is suspected of poisoning cattle in both countries (Everist 1981) and proved toxic when administered experimentally to chicks (Duncan et al 1957). B. glomerulifolia, another North American species, was experimentally toxic to mice and chicks (Duncan et al 1957), and B. pteronioides has been associated with cattle poisoning in the southwestern United States (Marsh et al 1920, Stegelmeier et al 2009). B. pteronioides toxicosis was produced in hamsters dosed with 100-200mg of the plant (Stegelmeier et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. halimifolia is an aggressive pioneer plant species that can rapidly colonize disturbed environments due to physiological adaptations that facilitate growth in saline and acidic soils (Parsons and Cuthbertson 2001). The species is also resistant to livestock herbivory due to the production of various intracellular toxins (Tokarnia et al 1992;Stegelmeier et al 2009). As a result of these invasive attributes, the Queensland Government has recognized B. halimifolia as a threat to the sustainability of agriculture and other land uses in Queensland (Wilson 2008).…”
Section: Introductionmentioning
confidence: 99%